2021
DOI: 10.1021/acsomega.1c01381
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Resolution of Methyltransferase-Mediated DNA Optical Mapping

Abstract: Interest in the human microbiome is growing and has been, for the past decade, leading to new insights into disease etiology and general human biology. Stimulated by these advances and in a parallel trend, new DNA sequencing platforms have been developed, radically expanding the possibilities in microbiome research. While DNA sequencing plays a pivotal role in this field, there are some technological hurdles that are yet to be overcome. Targeting of the 16S rRNA gene with amplicon sequencing, for instance, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…This work constitutes a proof of concept for the use of Fluorocode OM for detection of genomic elements, SCC mec of MRSA in particular, an idea that was previously examined by our group in silico . With previous findings by other optical mapping methods showing the detection of plasmids at 66 kbp, we have shown that OM as applied by Fluorocode is capable of detecting elements as short as 26 kbp .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This work constitutes a proof of concept for the use of Fluorocode OM for detection of genomic elements, SCC mec of MRSA in particular, an idea that was previously examined by our group in silico . With previous findings by other optical mapping methods showing the detection of plasmids at 66 kbp, we have shown that OM as applied by Fluorocode is capable of detecting elements as short as 26 kbp .…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In silico work by our group has produced interesting results regarding the identification of closely related strains, as well as the identification of relatively shorter genomic elements such as the SCCmec. 27 The bacteriophage genomes are between 40 and 70 kbp, while bacterial genomes are typically 1−4 Megabase pairs in length. It is of note that the scale of genomic elements to consider is different in OM compared to sequencing where the typical lengths are, for example, reads of 150 base pairs or amplicons of up to 1000 base pairs for PCR.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations